Analysis and optimization of the reform status of Yunnan seismic monitoring center stations - Zhirou Zhao; Yan Zhuang; Yanmei Wu; Zhen Li (地震科学进展, 2023)
The seismic monitoring center station is the basic unit of the seismic monitoring system. In the face of the new situation of reform and development and the establishment of a comprehensive emergency disaster relief system, the Yunnan Earthquake Agency completed the listing of the provincial seismic monitoring center stations at the end of September 2021, and determined the organization setting, function division and staffing of the center station, in order to better meet the needs of the seismic monitoring work in the development of earthquake prevention and disaster reduction in the new era. By reviewing the reform process of the Yunnan seismic monitoring center stations, this paper analyzes the current situation of the Yunnan seismic monitoring center station reform and the existing deficiencies, and puts forward corresponding optimization suggestions for the future development path. This is of great significance for improving the monitoring and forecasting capability and modernization level of the central stations, strengthening and standardizing the management of earthquake stations in Yunnan, and giving full play to the basic role of the seismic monitoring centers in the development of earthquake prevention and disaster reduction in the province.